Internet Network Monitoring in Oil Palm Irrigation Using MQTT Based on QoS Parameters - Edy Ervianto; Noveri Lysbetti Marpaung; Karin Dwi Purnomo; Khoirul Azmi; Sakti Hutabarat; Rahyul Amri; Linna Oktaviana Sari; Ika Mayla Sari (LPPM Universitas Potensi Utama, 2026)
Oil palm plantations require continuous and reliable monitoring to ensure efficient irrigation, yet many farmers still depend on manual watering methods that are time-consuming and inconsistent. To address this issue, this study develops an Internet of Things (IoT)-based irrigation monitoring system using the MQTT communication protocol to support real-time data delivery and automated control. The system integrates ESP32 microcontrollers, soil moisture and environmental sensors, HiveMQ Cloud as the MQTT broker, and Telegram Bot notifications. The research was conducted on a 27 m × 70 m oil palm plantation consisting of 24 trees. System testing was performed over seven days with two irrigation sessions daily, during which sensor data transmission and notification timestamps were recorded. QoS parameters including throughput, packet loss, delay, and jitter were analyzed using Wireshark. The results show that sensor data and irrigation notifications were consistently delivered within 3–5 seconds, demonstrating stable real-time communication. QoS evaluation indicates 0% packet loss, an average delay of 180 ms, and an average jitter of 0.17 ms, with an overall QoS index of 3.02, classified as “Satisfied.” These findings confirm that MQTT provides reliable communication performance in plantation environments and effectively supports automated irrigation monitoring for improving agricultural efficiency.